Kidney diseases and long non-coding RNAs in the limelight - Liu, Chenxin; Ma, Kuai; Zhang, Yunchao; He, Xing; Song, Linjiang; Chi, Mingxuan; Han, Zhongyu; Li, Guanhua; Zhang, Qinxiu; Liu, Chi (Frontiers in Physiology, 2022)
The most extensively and well-investigated sequences in the human genome are protein-coding genes, while large numbers of non-coding sequences exist in the human body and are even more diverse with more potential roles than coding sequences. With the unveiling of non-coding RNA research, long-stranded non-coding RNAs (lncRNAs), a class of transcripts >200 nucleotides in length primarily expressed in the nucleus and rarely in the cytoplasm, have drawn our attention. LncRNAs are involved in various levels of gene regulatory processes, including but not limited to promoter activity, epigenetics, translation and transcription efficiency, and intracellular transport. They are also dysregulated in various pathophysiological processes, especially in diseases and cancers involving genomic imprinting. In recent years, numerous studies have linked lncRNAs to the pathophysiology of various kidney diseases. This review summarizes the molecular mechanisms involved in lncRNAs, their impact on kidney diseases, and associated complications, as well as the value of lncRNAs as emerging biomarkers for the prevention and prognosis of kidney diseases, suggesting their potential as new therapeutic tools.